5m*5m+27m+34=0

Simple and best practice solution for 5m*5m+27m+34=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m*5m+27m+34=0 equation:


Simplifying
5m * 5m + 27m + 34 = 0

Reorder the terms for easier multiplication:
5 * 5m * m + 27m + 34 = 0

Multiply 5 * 5
25m * m + 27m + 34 = 0

Multiply m * m
25m2 + 27m + 34 = 0

Reorder the terms:
34 + 27m + 25m2 = 0

Solving
34 + 27m + 25m2 = 0

Solving for variable 'm'.

Begin completing the square.  Divide all terms by
25 the coefficient of the squared term: 

Divide each side by '25'.
1.36 + 1.08m + m2 = 0

Move the constant term to the right:

Add '-1.36' to each side of the equation.
1.36 + 1.08m + -1.36 + m2 = 0 + -1.36

Reorder the terms:
1.36 + -1.36 + 1.08m + m2 = 0 + -1.36

Combine like terms: 1.36 + -1.36 = 0.00
0.00 + 1.08m + m2 = 0 + -1.36
1.08m + m2 = 0 + -1.36

Combine like terms: 0 + -1.36 = -1.36
1.08m + m2 = -1.36

The m term is 1.08m.  Take half its coefficient (0.54).
Square it (0.2916) and add it to both sides.

Add '0.2916' to each side of the equation.
1.08m + 0.2916 + m2 = -1.36 + 0.2916

Reorder the terms:
0.2916 + 1.08m + m2 = -1.36 + 0.2916

Combine like terms: -1.36 + 0.2916 = -1.0684
0.2916 + 1.08m + m2 = -1.0684

Factor a perfect square on the left side:
(m + 0.54)(m + 0.54) = -1.0684

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| x=2y+2 | | 4y^2+16y+18=0 | | 3x+3=105 | | 6x+10=70-4x | | 2x=24-6x | | x-0.4=2x | | 6x-20=-14 | | 12=5+f | | 6x=90-3x | | 5x+7=9x+11 | | 10x+6=26 | | 8x-53=6x-5 | | 3x+7=27-2x | | 3z-9=4z-7 | | 51-2x=7x | | 2x=5-3x | | r+4.9=-5.4 | | 62-4x=5x+16 | | -2=12+x | | 18x=414 | | 11-9x=71-37x | | 3x=48-3x | | 8x+2x=9x+1 | | 5u^2+23u+32=0 | | 14x=322 | | -24=180x-165 | | (5w-9)(2+w)=0 | | 3x=-1.2 | | 2r^3-s^2-8r^2s^3= | | 2x^3-4x^2+5x= | | 51-2x=7x+22 | | (2x+1)(3x-2)=0 |

Equations solver categories